2011
DOI: 10.1007/s11266-010-9176-y
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream and Ethnic Volunteering by Korean Immigrants in the United States

Abstract: Asian immigrants accounted for one-eighth of the total U.S. population in 2009. With Asian immigrants having higher levels of education and income than average Americans, their potential contribution to American philanthropy will be even more significant. This study examines the volunteering patterns of Korean immigrants, one of the fastest growing segments of the Asian immigrant population in the United States. This study explains Korean immigrants' volunteering within ethnic and mainstream (American) organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 54 publications
0
25
1
Order By: Relevance
“…Schoeneberg (1985) found that the participation of immigrants in ethnic associations in West Germany helped or hindered integration, depending on the orientation of the association. However, North American studies found that immigrants who volunteered within their own ethnic congregations were simultaneously involved with mainstream organisations, thereby building both bridging and bonding social capital (e.g., Lee and Moon, 2011; Sinha et al , 2011).…”
Section: Volunteering By Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schoeneberg (1985) found that the participation of immigrants in ethnic associations in West Germany helped or hindered integration, depending on the orientation of the association. However, North American studies found that immigrants who volunteered within their own ethnic congregations were simultaneously involved with mainstream organisations, thereby building both bridging and bonding social capital (e.g., Lee and Moon, 2011; Sinha et al , 2011).…”
Section: Volunteering By Immigrantsmentioning
confidence: 99%
“…Indeed, one of the frequently-reported motivations to volunteer among the general population is the desire to make new friends (Clary and Snyder, 1999). By forging social ties and social capital through volunteering, immigrants can gain access to the job market (Baert and Vujic, 2016;Lee and Moon, 2011;Manatschal, 2015), learn the host society's social norms of reciprocity and connectivity, and build trust in social and political institutions. Putnam (2000) suggests that social capital consists of 'bonding' and 'bridging' social capital.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
“…Not surprisingly, most studies that focus on volunteering by immigrants mirror the positive effects of SES on the propensity to participate in secular volunteering (Handy and Greenspan, 2009;Sundeen, Garcia and Raskoff, 2009;Carabain and Bekkers, 2011;Lee and Moon, 2011;Sinha, Greenspan and Handy, 2011;Wang and Handy, 2014).…”
Section: Different Types Of Volunteeringdifferent Explanationsmentioning
confidence: 99%
“…Lack of knowledge can result in unreasonable fears regarding the donation of blood. Also, if the minority group has its own language, language barriers can arise and hinder blood donations of these potential donors (Polonsky et al 2013) especially as it was also found regarding volunteering for mainstream organizations of Asian immigrants in the United States (Lee and Moon 2011). With increasing assimilation to the new country, the lack of knowledge and language barriers could diminish, however, some groups, especially in big cities, live in subcultures that allow them to work, live, and communicate in their own language.…”
Section: Factors For Low Minority Participationmentioning
confidence: 99%